2001
DOI: 10.1002/job.87
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive divergence and shared mental models in software development project teams

Abstract: SummaryThis study examined the development of shared mental models in software development teams over time. Contrary to predictions, team members' mental models about the group's work and each other's expertise did not become more similar over time. Structural equation modelling revealed that as role differentiation increased in these teams, it led to a decrease in interaction and a corresponding decline in shared mental models. Implications for research on shared cognition and team development are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
223
3
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(238 citation statements)
references
References 28 publications
9
223
3
3
Order By: Relevance
“…In a software team, the members are jointly responsible for the end product and must develop shared mental models by negotiating shared understandings about both the teamwork and the task [28]. Project goals, system requirements, project plans, project risks, individual responsibilities, and project status must be visible and understood by all parties involved [21].…”
Section: Teamwork In Agile Development: the Scrum Teammentioning
confidence: 99%
“…In a software team, the members are jointly responsible for the end product and must develop shared mental models by negotiating shared understandings about both the teamwork and the task [28]. Project goals, system requirements, project plans, project risks, individual responsibilities, and project status must be visible and understood by all parties involved [21].…”
Section: Teamwork In Agile Development: the Scrum Teammentioning
confidence: 99%
“…This finding, based on a meta-analysis of 21 effect sizes across 1089 teams, suggests that distributed but compatible knowledge may be more appropriate to the complex task mental model. Distributed task knowledge may in turn imply a stronger need for a shared team model such that all members are minded of "who knows what", particularly insofar as divergence in task knowledge may also correspond with less time spent communicating (see for example, Levesque et al, 2001). Indeed, a recent study described by Hirschfeld et al (2006) found that better mastery of "teamwork knowledge" predicted better team task proficiency among US Air Officers in relation to a complex training task and higher observer ratings of effective teamwork after controlling for the former.…”
Section: Proposition 5 Cognitive States -Shared Cognitionmentioning
confidence: 99%
“…We also acknowledge that we have not attempted to cover concepts relating to shared mental models (e.g. Levesque et al 2001) or team mental models (e.g. Langan-Fox et al 2004) as part of theoretical framework.…”
Section: Toward An Integrated Representations Frameworkmentioning
confidence: 99%
“…Spatial Visualisation Spatial visualisation is described as a type of representation that can be used to solve mechanical problems (Hegarty et al 2003). Shared Mental Model Shared mental models are knowledge structures held by team members that enable task goals and team demands to be met (Cannon-Bowers et al 1993;Levesque et al 2001). …”
Section: Termmentioning
confidence: 99%